Systematic review on the applicability of principal analysis components for the study of movement in the older adult population - Moreira, J. (2022)
The principal component analysis (PCA) is a dimensionality reduction method that has identified significant differences in older adults' motion analysis, previously not detected by discrete exploration of biomechanical variables. This systematic review aims to synthesize the current evidence regarding PCA use in the study of movement in older adults (kinematics and kinetics), summarizing the tasks and biomechanical variables studied. From the search were retrieved 1685 results, and 19 studies were included for narrative review. Most of the included studies evaluated gait or orthostatic position. The main variables evaluated were spatio-temporal parameters, range of motion and ground reaction forces. A limited number of studies analyzed other tasks. Further research should focus the PCA application in tasks other than gait to understand older adults’ movement characteristics that has not been identified by discrete analysis.